2016
DOI: 10.1038/srep39407
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a TNF-α inducer MIC3 originating from the microneme of non-cystogenic, virulent Toxoplasma gondii

Abstract: Toxoplasma gondii is an opportunistic parasite with avirulent cystogenic and highly virulent non-cystogenic isolates. Although non-cystogenic strains are considered the most virulent, there are also marked genetic and virulence differences among these strains. Excretory-secretory antigens (ESAs) of T. gondii are critical for the invasion process and the immune response of the host. To better understand the differences in virulence between non-cystogenic T. gondii isolates, we studied ESAs of the RH strain (Typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…As mentioned above, TgGRA3 also plays an important role in parasite virulence (Craver and Knoll, 2007), a phenotype that may be linked to the pre-emption of key host immune molecules involved in controlling the outcome of parasite infection. In line with this point of view, proteomic studies identified TgGRA3 as a protein that was more highly expressed in virulent T. gondii strains than in less virulent strains (Qiu et al, 2016).…”
Section: Discussionmentioning
confidence: 76%
“…As mentioned above, TgGRA3 also plays an important role in parasite virulence (Craver and Knoll, 2007), a phenotype that may be linked to the pre-emption of key host immune molecules involved in controlling the outcome of parasite infection. In line with this point of view, proteomic studies identified TgGRA3 as a protein that was more highly expressed in virulent T. gondii strains than in less virulent strains (Qiu et al, 2016).…”
Section: Discussionmentioning
confidence: 76%
“…For example, the dense granule protein 7 (GRA7) induces MyD88-dependent NF-kB activation, which facilitates IL-12, TNF-α, and IL-6 production [32]. MIC3 is reported to induce TNF-α secretion and macrophage M1 polarization [52], whereas GRA15 expressed by Type II strains activates NF-kB, promoting the release of IL-12 [33], and GRA24 triggers the autophosphorylation of p38 MAP kinase and proinflammatory cytokine and chemokine secretion [34]. In contrast, TgIST interferes with IFN-γ induction by actively inhibiting STAT1-dependent proinflammatory gene expression indicating that the parasite is capable of both activating as well as inhibiting effector arms of the host immune response to impact its pathogenesis in vivo [53].…”
Section: Discussionmentioning
confidence: 99%
“…Toxoplasma gondii tachyzoites of RH strain were preserved in liquid nitrogen and resuscitated in C57BL/6 mice by intraperitoneal inoculation. ESA were prepared as described previously ( 28 ). The ESA were treated with AffinityPak Detoxi-Gel Endotoxin Removing Gel (Thermo, Fairlawn, OH, USA) to remove endotoxin.…”
Section: Methodsmentioning
confidence: 99%